PENGEMBANGAN KOMIK DIGITAL CHLOROPHYL SEBAGAI MEDIA PEMBELAJARAN PEDULI LINGKUNGAN SISWA SMA - BACHTIAR ADI SAPUTRA (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
The loss of a sense of responsibility that students have towards protecting and preserving nature is also a bad impact of the progress that has occurred in the present era. Therefore, the researchers took the initiative to develop a valid and practical "chlorophyll" digital comic-based learning media to be used in instilling concern for the surrounding environment. The method used in this research is developing research using ADDIE (Analyze, Design, Development, Implementation, and Evaluation) procedures. The development of this digital Chlorophyl comic consists of 12 pages starting from the opening page about the introduction of the main character, problems to solutions that can be done to protect the environment. Chlorophyl digital comics can be said to be valid with an average of 3.58 and have good criteria so that they can be used in the field with a few revisions that have been adapted to suggestions from experts. In addition, based on input from the validator with several notes of improvement and the assessment of student responses to chlorophyll digital comics, it was stated that it was very practical with a positive response of 80.59%. The conclusion obtained is that the digital chlorophyll comic that was developed is said to be valid with a value of 3.5 and stated to be very practical with a positive response of 80.59%. ABSTRAKHilangnya rasa tanggung jawab yang dimiliki para pelajar terhadap menjaga dan melestarikan alam juga menjadi dampak buruk dari kemajuan yang terjadi pada era masa kini. Oleh karena itu, peneliti bernisiatif untuk mengembangkan media pembelajaran berbasis komik digital chlorophyl yang valid dan praktis untuk digunakan dalam menanamkan kepedulian terhadap lingkungan sekitar. Metode yang digunakan dalam penelitian ini adalah penelitian mengembangkan dengan prosedur ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Pengembangan komik digital Chlorophyl ini terdiri atas 12 halaman mulai dari halaman pembuka tentang perkenalana tokoh utama, permasalahan hingga solusi yang bisa dilakukan untuk menjaga lingkungan hidup. Komik digital Chlorophyl dapat dikatakan valid dengan rata-rata yaitu 3,58 dan memiliki kriteria baik sehingga dapat digunakan di lapangan dengan sedikit revisi yang telah disesuaikan dengan saran dari para ahli. Selain itu berdasarkan masukan dari validator dengan beberapa catatan perbaikan dan penilaian angket respon siswa terhadap komik digital chlorophyl dinyatakan sangat praktis dengan respon positif sebanyak 80,59%. Kesimpulan yang didapatkan adalah komik digital chlorophyl yang dikembangkan dikatakan valid dengan nilai 3,5 dan dinyatakan sangat praktis dengan respon positif sebanyak 80,59%.